Simulation of imperfect competition by residual demand curves in oligopolistic electricity markets - Marulanda Guerra, Agustín (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In a competitive electricity market two kinds of generating companies coexist; according to their market power it possible to classify them in price-taking generating companies and leader generating companies. The optimal bidding of price-taking companies depends on the market clearing prices. On the other hand, the optimal bidding of leader companies depends on their corresponding residual demand curves, which capture how the market clearing price changes with the variation on the levels production of a particular generating company. The idea of this article is to assess the potential market power of a leader company when it decides to compete in quantities according to the Cournot model. A non-linear optimization problem has been used to model the lemel the dleader generating company. Finally, a realistic case study is presented and discussed.